Antitrust law and mergers - Hansen, David, 1987- (Routledge research in competition law., 2025)
"This book discusses the economic models and quantitative research involved in merger control forecasts, and the relationship between antitrust law and economics. Analysing qualitative and quantitative models within forecasts of merger control, the book applies the framework of antitrust law. This book proposes that economic modelling, econometrics application, and juridical application of antitrust law go hand in hand. Discussing the question of an economically rational application and enforcement of antitrust and merger control law, the book covers both the basic concepts and theory behind economic model forecasts, as well as the application of merger control law. It also takes a closer look at legal control options for competition authorities when making a forecast decision, and the associated problems of applying the law to this. The book will be of interest to researchers in the field of antitrust law, competition law, economics and corporate law"--